# How do I figure out what 4x+6=x+3 is

Yes

Posted by on

• Level 3:

An expert who has achieved level 3 by getting 1000 points

All-Star:

An expert that gotÂ 10 achievements.

MVP:

An expert that gotÂ 5 achievements.

Master:

An expert who has achieved Level 3.

• Master

Move the 6 to the right of the = sign by making it negative. That gives you 4x= x-3. Then move the x from the right to the left by making it negative and adding it to 4x. That gives you 3x=-3. Divide both sides by 3 to get x=-1.

Posted on Dec 01, 2014

Hi,
a 6ya expert can help you resolve that issue over the phone in a minute or two.
Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.
the service is completely free and covers almost anything you can think of.(from cars to computers, handyman, and even drones)
Goodluck!

Posted on Jan 02, 2017

×

my-video-file.mp4

×

## Related Questions:

### Let f(x)=7x 2 ?4x+8 and g(x)=?6+4x?7x 2 . What is f(x)+g(x) ?

f(x) + g(x) would just be the two functions added together.

f(x) + g(x) = 7x 2?4x+8 + (?6+4x?7x 2)

Sorry, I don't understand your initial functions.

Good luck.

Paul

Feb 07, 2017 | Homework

### 2(3-x)+3(x-1)=4x

x equals 1

First multiply the numbers outside the parentheses by what is inside the parentheses, which results in:

6 - 2x + 3x - 3 = 4x

then combine what you can:

6 - 3 = 3,
-2x + 3x = 1x

which leaves:

3 + x = 4x

Subtract the x on the left from the 4x on the right and you get:

3 = 3x

Divide by 3 to get the x alone

3 / 3 = 1

x = 1

Feb 02, 2014 | SoftMath Algebrator - Algebra Homework...

### 2x^5+4x^4-3x^2+7,7x^4-3x^3+x^2-9

5x -2(x-2) = 6 -2(-3x-3)
5x -2x +4 = 6 +6x +6 (use the distributive property)
3x + 4 = 6x + 12 (collect terms)
4 = 3x + 12 (subtract 3x from both sides to get all x on one side)
-8 = 3x (subtract 12 from both sides to get only x on one side)
-8/3 = x (divide both sides by 3 to get x by itself)

Check
5(-8/3) -2((-8/3)-2) = 6 - 2(-3(-8/3)-3)
-40/3 -2(-8/3-6/3) = 6 - 2(8-3)
-40/3 -2(-14/3) = 6 -2(5)
-40/3 + 28/3 = 6 - 10
-12/3 = -4 (yes)

Dec 19, 2010 | Answer Racing Ion Motorcycle Jersey 2010

### . x^3 - 4x^2 - 12x

Hii,you can use the following solution x^3 - 4x^2-12x=0 x(x^2-4x-12)=0 replacing -4x from -6x+2x x(x^2-6x+2x-12)=0
Now Factoring x(x(x-6) +2(x-6))=0 x(x-6)(x+2)=0 Solution is x=0, x-6=0,x+2=0 1) x=0 2) x-6=0 =>x=6 3) x+2=0 =>x=-2

May 05, 2010 | Vivendi Excel@ Mathematics Study Skills...

### 4x+3y=6 how do you solve for y

Hello,
I am not lecturing you but I would rather you understand how to do the manipulations involved in isolating a variable.
You want to isolate y, Ok
Start stripping it of all that is not y.

3y + 4x =6. (Addition is commutative, I can change the order of addition)
The term with y is added to 4x. If I want the term in y alone on one side I perform the inverse operation of addition, a substraction. I subtract 4x from both sides.
3y+4x-4x=6-4x. But 4x-4x=0, and we are left with

3y= - 4x+6

This operation is sometimes summarized as make one term change side while changing its sign

It would do no harm to put the right side of the foregoing equation in parentheses. I do that to avoid errors)

3y= (-4x+6).

Now y is multiplied by the number 3. To isolate y I have to perform the inverse operation of the multiplication, namely the division by 3

3y/3 =(-4x+6)/3. The left hand side is just y

y= (-4x+6)/3.

While result is correct, I can also open the parentheses
y= -4x/3 +6/3
y= -(4/3)*x +2.

Hope it helps.

Oct 22, 2009 | Texas Instruments TI-89 Calculator

### Find the value of the variable ''x'' 6x+6=4x+12

6x+6=4x+12
Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.
6x+6-4x=12
Since 6x and -4x are like terms, add -4x to 6x to get 2x.
2x+6=12
Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.
2x=-6+12
Add 12 to -6 to get 6.
2x=6
Divide each term in the equation by 2.
(2x)/(2)=(6)/(2)
Simplify the left-hand side of the equation by canceling the common factors.
x=(6)/(2)
Simplify the right-hand side of the equation by simplifying each term.
x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

### Algebra

Paul 3 years younger to his friend peter. In seven years, the product of their ages would be 5 more than the product of their ages 5 years ago. How old are they now?

Oct 31, 2008 | Texas Instruments TI-30XA Calculator

### Simplify

[3(x-5)-4(-3x+2)]-[4(6-x)]
[(3x-15)-(12x+8)]-(24-4x)
(-9x-23)-(24-4x)
-13x-(-1)

Sep 13, 2008 | Texas Instruments TI-84 Plus Calculator

### What does this error code mean 37,006.42:4545. Printer is Xerox 8550

37,006.42 The Drum Heater is drawing less power than expected.

• If the problem persists, follow the procedure below.
Table 1. 37,0XX.4x Troubleshooting Reference Table Applicable Parts
Wiring and Plug/Jack References
Electronics Module, Figure 6
Electronics Module, Figure 6
Preheater, PL 2.0
Electronics Module Power, Figure 7

Apr 13, 2008 | Office Equipment & Supplies

## Open Questions:

#### Related Topics:

938 people viewed this question

Level 3 Expert

Level 3 Expert